Sobre corporalidad, visión y procesos noéticos en los Hermetica y ciertos paralelos platónicos - Cano Cuenca, Jorge (Pontificia Universidad Católica del Perú, 2025)
“On Corporeality, Sight and Noetic Processes in the Hermetica and Certain Platonic Parallels”. Based on treatises I and XIII of the Corpus Hermeticum (“Poimandres” and “On a Mountain: An Esoteric Discourse Concerning Palingenesis and the Requirement of Silence”) and Nag Hammadi VI (“The Ogdoad and the Ennead”), this article addresses the physical (bodily and sensorial) conditions necessary for Hermetic revelation and how the role played by sensible vision as an opening to a fully noetic dimension has its roots in Plato’s theory of vision. Although what the Hermeticists understand by knowledge is not so much an argumentative and rational learning as a transformative, directly relational and unitive experience (Hermetic gnosis), a clear parallel can be established with the function of the Sun, light and the fiery nature of the eye in key passages of Phaedrus, Republic and Timaeus.

Partiendo los testimonios fundamentales de los tratados I y XIII del Corpus Hermético (“Poimandres” y “Discurso secreto en el páramo sobre la regeneración y la promesa de silencio”) y Nag Hammadi VI (“La Ogdóada y la Eneáda”) se abordan en este artículo las condiciones físicas (corporales y sensoriales) necesarias que hacen posible la revelación hermética y cómo el papel que desempeña la visión sensible como apertura a una dimensión plenamente noética y no sensible hunde sus raíces en la teoría platónica de la visión. Aunque lo que los herméticos entienden por conocimiento no es tanto un saber argumentativo y racional como una experiencia transformadora, inmediatamente relacional y unitiva (la gnosis hermética), cabe establecer un claro paralelo con la función del sol, la luz y la naturaleza ígnea del ojo en importantes pasajes de Fedro, República y Timeo.
On Corporeality, Sight and Noetic Processes in the Hermetica and Certain Platonic Parallels
Keywords: Hermeticism; Corpus Hermeticum; Plato and Platonism; Philosophy in the Roman Empire; Aesthetic and noetic vision; Hermetismo; Corpus Hermético; Platón y el platonismo; Filosofía en época imperial romana; Visión sensible y noética; https://purl.org/pe-repo/ocde/ford#6.03.01